Nursing Care Model Development by Cope Approach for Reducing Parent’s Hospitalization Stress with Cancer Children - Ilya Krisnana (Universitas Airlangga, 2013)
Introduction: Hospitalization stress on child affect on their parents. Parent empowerment is the important aspect to develop in nursing care for reducing hospitalization stress. The objective of this study was to develop the nursing care model of reduction hospitalization stress through the COPE (creating opportunity for parent empowerment) approach on the parent whose child was diagnosed cancer.Methods: This study used explanative research with cross sectional design. The population were parents whose child was diagnosed cancer in pediatric hematological ward RSUD Dr. Soetomo Surabaya, conducted on 3–15th May 2012. Sample were 30 mother who met inclusion criteria: 1) toddler and preschool age, 2) first time admition on Bona 1 or Bona 2, 3)read and write well and 4) noncritical condition. The independent variable were antecedens (attitude, social economic status, motivation), diffusion of innovation, empowerment (knowledge, participation, skill and environment). The dependent variable was parent’s hospitalization stress. Data were collected by using questionnaires and observation. The data were analyzed by PLS (Partial Least Square) with loading factor =0.5 and T-statistic=1.96.Results : The result showed that antecedens factors affected to COPE diffusion of innovation process. Motivation was the strongest factor to influence the diffusion and innovation process (path coeffi cient=0.450;T-stat=5.278). The diffusion of innovation process affected to empowerment variable (path coeffi cient=0.487; T-stat=6.507).Conclusion: It can be concluded that environment was the strongest factor as the compiler component of empowerment. Environment include physical and non-physical component. Empowerment affected to parent’s hospitalization stress with path coefficient=0.360 and T-statistik=4.980.Nursing Care Model Development by Cope Approach for Reducing Parent’s Hospitalization Stress with Cancer Children